Advancing resilience: An integrative, multi-system model of resilience. (1st June 2017) - Liu, Jenny J.W.; Reed, Maureen; Girard, Todd A.
Abstract: In this paper, we examine the dynamic nature of the resilience process as an interaction between individuals and their larger socio-ecological context. We introduce a novel, multi-systems model of resilience that addresses limitations within existing models, clarifies ambiguity brought on by heterogeneous definitions of resilience, and recognizes resilience as a process across the lifespan. This model includes intra-individual, interpersonal, and socio-ecological variables, and highlights the interactive process of resilience that is dynamic and multi-dimensional in nature. Highlights: Resilience is an interactive process between individuals and the larger community. Research suffers from ambiguous definitions and variability in measuring outcomes. A multi-system model is proposed to address limitations in resilience research. Proposed systems are intra-individual, interpersonal, and socio-ecological.